Preschool attendance and early childhood development outcomes in the first year of school for Aboriginal and non-Aboriginal children in New South Wales, Australia: IJPDS (2017) Issue 1, Vol 1:104, Proceedings of the IPDLN Conference (August 2016) - Jorgensen, Mikaela; Falster, Kathleen; Hanly, Mark; Goldfeld, Sharon; Jorm, Louisa; Craven, Rhonda (International Journal of Population Data Science, 2017)
ABSTRACT Objectives A key target to reduce the gap in early childhood outcomes between Australian Aboriginal and non-Aboriginal children has been to increase preschool enrolment rates, particularly in remote communities. However, there is little population-based information on preschool attendance and its impact on child development for Aboriginal children specifically. This study aims to examine: (i) the characteristics of children, families and areas associated with preschool attendance; and (ii) the association between preschool attendance and childhood development in the first year of school for Aboriginal and non-Aboriginal children in Australia’s most populous state, New South Wales (NSW). Approach Routinely-collected birth registration, perinatal, health and education data were used to create a linked dataset consisting of an almost complete population of children known as the ‘Seeding Success’ cohort. These children were born in NSW and had an Australian Early Development Census (AEDC) checklist completed by their teacher in their first year of school in NSW in 2009 and 2012 (n=154,936). Multilevel Poisson regression modelling was used to determine child-, family- and area-level characteristics associated with preschool attendance in the year before starting school. The association between preschool attendance and childhood development in the first year of school, as measured across five AEDC developmental domains, was also examined. Results 71% of Aboriginal children attended preschool in the year before school (95% CI: 70% to 72%) compared with 76% of non-Aboriginal children (95% CI: 76% to 77%). The prevalence of preschool attendance was lower in major cities compared with regional and remote areas, with 65% of Aboriginal children attending preschool in major cities compared with 73% in outer regional and 79% in remote areas. Factors associated with preschool attendance in the year before starting school included being non-Aboriginal, speaking English as a first language, having a mother with a partner, having fewer older siblings, living in a more remote area and living in a less socioeconomically disadvantaged area. After adjusting for potentially confounding factors, Aboriginal children who attended preschool were more likely to be developmentally ‘on track’ compared with Aboriginal children who did not attend preschool, in four of the five AEDC domains. Conclusion The barriers to preschool attendance for Aboriginal children living in major cities should be further explored. Targeted support for families and areas where preschool attendance is lower is likely required to ensure children have access to the apparent benefits of preschool education.